‘The struggle for imagination’. On the ecumenical implications of an aspect of Bible interpretation - Sawicki, Bernard (The Bible as a meeting place for Christian denominations, 2022)
This article addresses the role of imagination in the reception and interpretation of the Bible. It draws on two traditions of reading and understanding the Bible – the monastic one from the first centuries of ancient Christianity, which is still an important point of reference for Eastern Christianity today, and the Anglican-Presbyterian one. The starting point for the juxtaposition of these two traditions is a definition of imagination drawn from biblical Hebrew hermeneutics, which allows the topic to be framed in the context of spiritual warfare. On the part of the Eastern monastic tradition, this is discussed mainly on the basis of the writings of Evagrius of Pontus, expanded by the opinions of some Church Fathers. Western views are expressed on the basis of the works of Avis, Brookman, Ricoeur, Tacy and others. One of their aspects is the perception of the biblical discourse as myth and the consequences related to this. The conclusion emphasises the importance of imagination in Christianity today, but also shows the different approach to imagination in the two traditions.